(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
This paper explores the theme of community and its connection with solidarity. In an age of globalisation that tends to socio-economic development alone, Edith Stein's theory of community brings to the fore the relational character of our being persons who live with others. Stein's concept of community points to the experience of being and living with others in a way that helps us "promote a person-based and community-oriented process of world-wide integration that is open to transcendence," a project that Benedict XVI proposes in Caritas in Veritate. While many theories on community stress collectivism and the common good as being above the individual person, Stein's theory of community helps us regard both the individual person and community as central to achieving solidarity.